2023
DOI: 10.3390/ani13142300
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Assay Methods to Quantify ROS and Enzymatic Antioxidants in Erythrocytes and Spermatozoa of Small Domestic Ruminants

Abstract: The present review aims to provide an overview of the assay methods for the quantification of ROS and principal enzymatic antioxidants as biomarkers of oxidative stress in erythrocytes and spermatozoa of small domestic ruminants. A complete literature search was carried out in PubMed, Scopus and the World Wide Web using relevant keywords and focusing on the last five years (2018–2023). Among spectrophotometry, fluorometry and chemiluminescence, the most widely used method for ROS assay is fluorometry, probably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Spermatozoa are highly susceptible to the detrimental effects of reactive oxygen species (ROS) primarily due to the substantial presence of unsaturated fatty acids in their cell membranes. ROS promote the peroxidation of lipids, leading to a loss of membrane integrity and subsequently increasing permeability [ 20 ]. Additionally, spermatozoa are particularly vulnerable to oxidative attacks because their cellular membranes contain a high quantity of polyunsaturated fatty acids (PUFAs), which are highly sensitive to lipid peroxidation.…”
Section: Free Radicals In Small Ruminant’s Semenmentioning
confidence: 99%
See 1 more Smart Citation
“…Spermatozoa are highly susceptible to the detrimental effects of reactive oxygen species (ROS) primarily due to the substantial presence of unsaturated fatty acids in their cell membranes. ROS promote the peroxidation of lipids, leading to a loss of membrane integrity and subsequently increasing permeability [ 20 ]. Additionally, spermatozoa are particularly vulnerable to oxidative attacks because their cellular membranes contain a high quantity of polyunsaturated fatty acids (PUFAs), which are highly sensitive to lipid peroxidation.…”
Section: Free Radicals In Small Ruminant’s Semenmentioning
confidence: 99%
“…O’Flaherty et al [ 28 ] have reported that these reactions are associated with impaired sperm function, leading to infertility and alterations in sperm motility in ruminants and equines, as well as affecting sperm capacitation. Within proteins, the specific ratio of oxidized to reduced thiol groups (SS/SH) is essential to ensure proper protein functions, but this balance can be affected by ROS [ 20 , 29 ]. Therefore, the quantification of total thiols and/or glutathione (GSH) in cells is critical for monitoring the level of OS.…”
Section: Free Radicals In Small Ruminant’s Semenmentioning
confidence: 99%